PENGEMBANGAN DISPOSISI DAN PEMAHAMAN KONSEPTUAL MATEMATIS SISWA MELALUI PENDEKATAN ANTISIPASI DIDAKTIS DI SMA - Lusiana, Lusiana; Sugiatno, Sugiatno; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out the development of mathematical disposition and conceptual understanding of student related the concept of trigonometric comparison values of special angels material after giving them learning using didactical anticipation approach in Senior High School 1 Sambas in the academic year 2015/2016. The method used is pedagogical action research that adapts the Stringer model with two cycles. The subject in this research is the students of grade XI Science 3 Senior High School 1 Sambas as much as one class chosen purposively. Instruments used to collect data in this research consisted of test questions to measure students mathematical conceptual understanding, and questionnaires to find out mathematical disposition of students giving them learning using didactical anticipation approach. Based on data analysis, the result are: 1) mathematical disposition increased with average of 79.73 which was categorized as advanced; 2) mathematical conceptual understanding increased with average of 84.84 which was categorized as advanced; 3) steps of learning process 100% done that include preliminary 3.63, core activities 3.8, and closing activities 3.5, this categorized very well with an overall average rating of 3.73. Keywords   :  Mathematical Disposition, Mathematical Conceptual Understanding, Didactical Anticipation